Immunomodulatory and Anti-fibrotic Effects Following the Infusion of Umbilical Cord Mesenchymal Stromal Cells in a Critically Ill Patient With COVID-19 Presenting Lung Fibrosis: A Case Report - Silva, Kátia Nunes da; Pinheiro, Priscila Carvalho Guedes; Gobatto, André Luiz Nunes; Passos, Rogério da Hora; Paredes, Bruno Diaz; França, Luciana Souza de Aragão; Nonaka, Carolina Kymie Vasques; Barreto-Duarte, Beatriz; Araújo-Pereira, Mariana; Tibúrcio, Rafael; Cruz, Fernanda Ferreira; Martins, Gabriele Louise Soares; et al. (Frontiers in Medicine, 2021)
Background: The patients with coronavirus disease 2019 (COVID-19) associated with severe acute respiratory distress syndrome (ARDS) may require prolonged mechanical ventilation which often results in lung fibrosis, thus worsening the prognosis and increasing fatality rates. A mesenchymal stromal cell (MSC) therapy may decrease lung inflammation and accelerate recovery in COVID-19. In this context, some studies have reported the effects of MSC therapy for patients not requiring invasive ventilation or during the first hours of tracheal intubation. However, this is the first case report presenting the reduction of not only lung inflammation but also lung fibrosis in a critically ill long-term mechanically ventilated patient with COVID-19. Case Presentation: This is a case report of a 30-year-old male patient with COVID-19 under invasive mechanical ventilation for 14 days in the intensive care unit (ICU), who presented progressive clinical deterioration associated with lung fibrosis. The symptoms onset was 35 days before MSC therapy. The patient was treated with allogenic human umbilical-cord derived MSCs [5 × 107 (2 doses 2 days interval)]. No serious adverse events were observed during and after MSC administration. After MSC therapy, PaO2/FiO2 ratio increased, the need for vasoactive drugs reduced, chest CT scan imaging, which initially showed signs of bilateral and peripheral ground-glass, as well as consolidation and fibrosis, improved, and the systemic mediators associated with inflammation decreased. Modulation of the different cell populations in peripheral blood was also observed, such as a reduction in inflammatory monocytes and an increase in the frequency of patrolling monocytes, CD4+ lymphocytes, and type 2 classical dendritic cells (cDC2). The patient was discharged 13 days after the cell therapy. Conclusions: Mesenchymal stromal cell therapy may be a promising option in critically ill patients with COVID-19 presenting both severe lung inflammation and fibrosis. Further clinical trials could better assess the efficacy of MSC therapy in critically ill patients with COVID-19 with lung fibrosis associated with long-term mechanical ventilation.